DETERMMINAN DISFUNGSIONAL AUDIT (Studi Empiris Pada Kantor Akuntan Publik Di Jawa Tengah) - Gadis Trianita Hening, 12.05.52.0180; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2016)
The research objective was to examine the influence of locus of control eksternal, the auditor's performance, organizational commitment, time budget pressure, and the dignity of the dysfunctional audit on Public Accounting Firm (KAP) in Central Java. The sample in this study is contained in the auditor Public Accounting Firm (KAP) in Central Java. The sampling technique using a convenience sampling, the latest data the number of auditors, both in the level of junior, senior, and the manager can not be known with certainty. Methods of data analysis using multiple linear regression analysis. The results showed that the locus of control eksternal and time budget pressure positive and significant effect on the behavior of dysfunctional audit. Performance auditors showed that the influence of the negative and not significant to audit dysfunctional behavior. While the commitment of the organization to have a significant negative effect on the behavior of dysfunctional audit. And self-esteem showed positive and significant impact on the behavior of dysfunctional audit.Keywords: Locus Of Control Eksternal, The Auditor's Performance, Organizational Commitment, Time Budget Pressure, Self-Esteem, Dysfunctional Audit